2010
DOI: 10.1002/app.32844
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of superhydrophobic wood surfaces

Abstract: Superhydrophobic films were developed on wood substrates with a wet chemical approach. Growth of zinc oxide (ZnO) nanorods was found differentially in the cross-sectional walls and inner lumenal surfaces. The surface roughness of the prepared films on the inner lumenal surface conformed to the Cassie-Baxter wetting model, whereas the roughness across the microsurface of the cell wall was in conformity with the hydrophobic porous wetting model. The space between the ZnO nanorods and the microstructure of the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 18 publications
(20 reference statements)
0
54
0
Order By: Relevance
“…Based on the results, it can be concluded that the hydrophobic layers and the oil coating significantly increase the hydrophobicity of natural wood surfaces [14,77]. However, the increase in hydrophobicity after coating application [15,50,52] does not necessarily indicate long-term functionality during exposure to weathering (Figures 6 and 7). In general, the use of hydrophobic layers can only be recommended for sheltered wood (i.e., without leaching of extractives by water), which can lead to easier maintenance and cleaning during use.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on the results, it can be concluded that the hydrophobic layers and the oil coating significantly increase the hydrophobicity of natural wood surfaces [14,77]. However, the increase in hydrophobicity after coating application [15,50,52] does not necessarily indicate long-term functionality during exposure to weathering (Figures 6 and 7). In general, the use of hydrophobic layers can only be recommended for sheltered wood (i.e., without leaching of extractives by water), which can lead to easier maintenance and cleaning during use.…”
Section: Resultsmentioning
confidence: 96%
“…This could be potentially prevented using hydrophobic self-cleaning coatings in combination with UV stabilization of the underlying wood. Although more studies have been done to investigate the possibilities of wood surface hydrophobic modification [15,[50][51][52], their long-term efficiency during outdoor exposure should also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…The space between the ZnO nanorods and the microstructure of the wood surface constituted the nanoscale and microscale roughness of the ZnO nanofilm, respectively. The water contact angle of the prepared wood surfaces was up to 153.5 degrees (Wang et al, 2011). Increased UV protection with nanometal oxides that allow wood texture to remain seen and higher resilience to scratch and abrasion with use of different nanoparticle shapes are some of the applications that are reviewed here (Nikolic et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, based on this principle, highly hydrophobic or superhydrophobic surfaces have been successfully fabricated on cellulose-based materials and solid wood substrates by roughening the surface with inorganic nanoparticles in combination with low-surface energy treatments (Li et al 2010;Hsieh et al 2011;Jin et al 2011;Sun et al 2011;Wang et al 2011;Fu et al 2012;Jin et al 2012;Wang et al 2012;Wang et al 2014). However, many of these processes involve multistep procedures or expensive reagents, special equipment, and harsh experimental conditions.…”
Section: Introductionmentioning
confidence: 99%